The assessment of the status of the prooxidant-antioxidant system in patients with chronic generalized periodontitis in the post-сovid period - Matviykiv, T. I.; Rozhko, M. M.; Tokaryk, G. V. (Actual Dentistry, 2022)
Resume. The article presents the results of the study of the intensity of free radical processes (FRP) and the activity of antioxidant systems (AOS) in the blood serum of people who were infected with the Sars-Cov-2 virus. The study of the initial level of TBC-active products and the increase in their concentration in the oral fluid of the research group, it showed that their value was significantly higher compared to the indicators of the representatives of the control group, which indicates an increase in lipid peroxidation. It was established that the catalase index and SOD activity of the salivary glands are significantly lower in the infected persons compared to similar indicators of the control group, which are due to long-term stress exposure, high emotional stress and depressive states of the patients and indicates the exhaustion of the antioxidant system. At the same time, there is an increase in such enzymes as glutathione peroxidase and glutathione reductase. It was found that the intensity of free radical processes and the imbalance of antioxidant systems increases with the deepening of immunodeficiency and with the progression of periodontal pathology.